Integrasi Sosial Masyarakat Golongan Miskin Di Perkotaan - Raras Kusuma (Law Department, Sharia and Law Faculty., 2022)
The poor are seen as incapable and helpless people because poverty has become a culture for them. This situation is caused by structural constraints that are still shackled in the community. In the process of survival in society, each group is required to establish and develop social relationships based on the complexity of the interests of each group in order to create social integration. The condition of the poor living in urban areas is at the subsistence level and below subsistence. So that this triggers pressure that causes the poor to be in a disadvantaged position. In an effort to uphold justice to create a form of social integration in urban areas, an interconnected environment is needed. In the reality that is found, the life of the community between groups in urban areas has not yet occurred as a perfect assimilation. Imperfect assimilation results in problems that trigger inter-group conflicts, such as discrimination by various parties or groups against the poor who are powerless. This article discusses how the poor can be integrated with various aspects of life and urban groups in the existing reality.